2019
DOI: 10.1109/tcomm.2019.2900676
|View full text |Cite
|
Sign up to set email alerts
|

Simple Approximations of the SIR Meta Distribution in General Cellular Networks

Abstract: Compared to the standard success (coverage) probability, the meta distribution of the signal-to-interference ratio (SIR) provides much more fine-grained information about the network performance. We consider general heterogeneous cellular networks (HCNs) with base station tiers modeled by arbitrary stationary and ergodic non-Poisson point processes. The exact analysis of non-Poisson network models is notoriously difficult, even in terms of the standard success probability, let alone the meta distribution. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…As discussed in [8], the direct computation of the meta distribution in (8) is not straightforward. A general approach to overcome this issue is to capitalize on the Gil-Pelaez inversion theorem [15], which allows one to formulate the meta distribution as a function of the moments of the (conditional) coverage probability in (9).…”
Section: Computation: Gil-pelaez Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in [8], the direct computation of the meta distribution in (8) is not straightforward. A general approach to overcome this issue is to capitalize on the Gil-Pelaez inversion theorem [15], which allows one to formulate the meta distribution as a function of the moments of the (conditional) coverage probability in (9).…”
Section: Computation: Gil-pelaez Methodsmentioning
confidence: 99%
“…In the present paper, motivated by these considerations and by [9], we generalize the IDT approach for computing the meta distribution in non-Poisson cellular networks. We consider a recent and improved definition of the coverage probability, which allows one to account for the signal quality during the cell association and data transmission phases [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The homogeneous infinite Poisson point process (HPPP) is a very popular choice for the distribution of the spatial locations of terrestrial transceivings due to its simplicity and tractability [3] - [5], whereas recently has been adopted for the spatial modeling of UAV networks [6] - [8]. In particular, in [6], a coverage and rate analysis is conducted by assuming that UAVs are deployed in a plane above the ground forming a PPP.…”
Section: A Motivations and Related Workmentioning
confidence: 99%
“…Recently, it has been observed that the coverage of cellular networks based on non-PPP models can be approximated by adjusting the SIR threshold of the corresponding network based on a PPP model with the same density. The adjusting coefficient is called SIR gain and the method is called ASAPPP [13][14][15][16][17][18][19][20]. Using this method, the SIR gain for the MHCP modelled network can be expressed as…”
Section: The Asappp Approach For Single-tier Mhcp Networkmentioning
confidence: 99%
“…[17] derives the coverage probability of the two-tier HCN modelled by PPP and PCP, but the derivation process is too complicated and the results can only be obtained by numerical computation. [18] and [19] analyze the distribution of the conditional success probability for HCN based on PPP and non-PPP, respectively. According to the principle of nearest BS access, [20] investigate the approximate SIR distribution of K-tier HCNs with the use of ASAPPP method.…”
Section: Introductionmentioning
confidence: 99%